Income Inequality, Fiscal Decentralization and Transfer Dependency - Goerl, Caroline-Antonia.; Seiferling, Mike. (Washington, D.C. : International Monetary Fund, 2014)
Within the context of reigniting post crisis macroeconomic growth, income inequality has emerged as a topic of significant interest for both academics and policymakers (Bastagli, Coady, and Gupta, 2012) This study builds on past literature on fiscal decentralization suggesting that redistribution is most effectively carried out at sub-central levels of government. Using the IMF's multi-sector Government Finance Statistics Yearbook database, this paper tests the impact of decentralized redistribution on income inequality for a globally representative sample of countries since 1980. The findings suggest that the decentralization of government expenditure can help achieve a more equal distribution of income. However, several conditions need to be fulfilled: i) the government sector needs to be sufficiently large, ii) decentralization should be comprehensive, including redistributive government spending, and, iii) decentralization on the expenditure side should be accompanied by adequate decentralization on the revenue side, such that subnational governments rely primarily on their own revenue sources as opposed to intergovernmental transfers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet